The verbal act in the heritage text "the text of Ismail bin Abi Al-Jahm and Hisham bin Abdul Malik as a model" - a pragmatic study - Al-Farraj, Rashid Hamoud (Journal of Arabic Language Sciences and Literature, 2024)
This research discusses the speech act in the traditional text ‘The text of Ismail bin Abi al-Juhm and Hisham bin Abdul Malik as a model,’ studying it from a pragmatic perspective. It begins by dividing the speech act into locutionary, illocutionary, and perlocutionary acts, and considers its function, ethics, and aims to highlight the text in several aspects including: its documentation, the category it has been placed in by authors, and clarifies the interaction of the text between the speakers and the extent of their connection and relationship, and the commitment of each to the ethics of the speech act, and demonstrates each one’s method of persuading the other through the speech act by explaining its function.